Dental Pulp Cell Behavior in Biomimetic Environments. (November 2015) - Smith, J.G.; Smith, A.J.; Shelton, R.M.; Cooper, P.R.
There is emerging recognition of the importance of a physiologically relevant in vitro cell culture environment to promote maintenance of stem cells for tissue engineering and regenerative medicine purposes. In vivo, appropriate cellular cues are provided by local tissue extracellular matrix (ECM), and these are not currently recapitulated well in vitro using traditional cultureware. We therefore hypothesized that better replication of the in vivo environment for cell culture and differentiation could be achieved by culturing dental pulp cells with their associated ECM. Primary dental pulp cells were subsequently seeded onto pulp-derived ECM-coated cultureware. While at up to 24 h they exhibited the same level of adherence as those cells seeded on tissue culture–treated surfaces, by 4 d cell numbers and proliferation rates were significantly decreased in cells grown on pulp ECM compared with controls. Analysis of stem cell and differentiation marker transcripts, as well as Oct 3/4 protein distribution, supported the hypothesis that cells cultured on ECM better maintained a stem cell phenotype compared with those cultured on standard tissue culture–treated surfaces. Subsequent differentiation analysis of cells cultured on ECM demonstrated that they exhibited enhanced mineralization, as determined by alizarin red staining and mineralized marker expression. Supplementation of a 3% alginate hydrogel with pulp ECM components and dental pulp cells followed by differentiation induction in mineralization medium resulted in a time-dependent mineral deposition at the periphery of the construct, as demonstrated histologically and using micro–computed tomography analysis, which was reminiscent of tooth structure. In conclusion, data indicate that culture of pulp cells in the presence of ECM better replicates the in vivo environment, maintaining a stem cell phenotype suitable for downstream tissue engineering applications.